2021
DOI: 10.3390/brainsci11030326
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning Stimulus Intensity Alters Paired-Pulse TMS Evoked Potentials

Abstract: Motor cortex (M1) paired-pulse TMS (ppTMS) probes excitatory and inhibitory intracortical dynamics by measurement of motor-evoked potentials (MEPs). However, MEPs reflect cortical and spinal excitabilities and therefore cannot isolate cortical function. Concurrent TMS-EEG has the ability to measure cortical function, while limiting peripheral confounds; TMS stimulates M1, whilst EEG acts as the readout: the TMS-evoked potential (TEP). Whilst varying preconditioning stimulus intensity influences intracortical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Our observations of TEP SICI are only in partial agreement with previous studies. These mostly reported a suppression of P60 but also found a decrease of P30 [30-32], and a decrease [30] or an increase of N45 [28, 31, 32]. In a very recent publication, Rawji et al additionally showed a suppression of N15 (here N17) and P180 [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observations of TEP SICI are only in partial agreement with previous studies. These mostly reported a suppression of P60 but also found a decrease of P30 [30-32], and a decrease [30] or an increase of N45 [28, 31, 32]. In a very recent publication, Rawji et al additionally showed a suppression of N15 (here N17) and P180 [28].…”
Section: Discussionmentioning
confidence: 99%
“…These mostly reported a suppression of P60 but also found a decrease of P30 [30-32], and a decrease [30] or an increase of N45 [28, 31, 32]. In a very recent publication, Rawji et al additionally showed a suppression of N15 (here N17) and P180 [28]. Contrary to all above-mentioned studies, the early study of Paus et al reported no effect of SICI in TEPs [91], whereas two more recent studies only found a reduction of late TEP components N100 and P180/P300 [29, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another undisclosed methodological issue that deserves further investigation is related to the influence of TMS intensity (either of the first and the second pulse) on the effectiveness of PAS, notwithstanding the recent evidence of its crucial role, especially in paired-pulse TMS paradigms or when frontal TEPs are measured (e.g., Bäumer et al, 2009;Zanon et al, 2018;Rawji et al, 2021). For future studies aiming to develop novel frontal PAS, we suggest to carefully consider these methodological works on the importance of TMS intensity, thus to select the better parameters to stimulate (and modulate) the target cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EEG responses due to direct activation of cutaneous afferent fibres by TMS are very small when somatosensory input is mimicked by electrical stimulation of the scalp or even absent when the TMS pulse is considered (Gosseries et al, 2015;Sarasso et al, 2020). Even if responses caused by indirect brain activation due to sensory input are present, they are represented by stereotypical vertex potentials in the 100-200 ms range, irrespective of the stimulation site, compatible with saliency-related multimodal responses (Mouraux & Iannetti, 2009;; these show marked topographical differences compared to TEPs, the latter being characterized by maximal activity at the stimulation site and by the larger amplitude of signals of <100 ms (Belardinelli et al, 2019;Mancuso et al, 2021;Rawji et al, 2021). Beyond these issues, there is no general agreement on the preprocessing pipeline for removing early TMS-locked artifacts (i.e.…”
Section: Tms-eegmentioning
confidence: 99%